MENINGKATKAN KEMAMPUAN BAHASA INGGRIS SISWA MI MELALUI STRATEGI PEMBELAJARAN AKTIF - Erina Hastuti; Athingatul Adhiyani; Sa’ada Turroh Mania (Universitas Nahdlatul Ulama Al Ghazali Cilacap, 2025)
This study aims to examine the effectiveness of active learning strategies in improving the English language skills of elementary school (MI) students. Mastery of English from an early age is crucial for establishing the foundation for global communication. However, monotonous and less interactive learning often hinders student competency development. This study employed a descriptive qualitative method with a literature review approach and limited observation. Various active learning strategies, such as role-play, group discussions, and educational games, were used to enhance student participation. The results showed an increase in student motivation, vocabulary comprehension, and confidence in speaking English. These strategies provided a fun learning experience and boosted student confidence. The implications of this study emphasize the importance of innovative learning methods in elementary English language education.